Effect of cupping therapy on the level of pain and neuromuscular variables in women with low back pain - Spinoso, Deborah Hebling; Pereira, Leticia Carvalho (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: Cupping therapy is a common technique in the field of traditional Chinese medicine, which through sucking on the skin mainly results in pain relief. Objectives: To analyze the effect of cupping therapy on pain intensity, muscle co-contraction and trunk extensor muscle strength in women with low back pain. Methods: 26 women participated, divided into: LBPgroup (n = 13), and control group (n = 13). The level of pain, isometric strength of trunk extensor muscles and co-contraction of superficial and deep trunk muscles were evaluated. The cupping therapy treatment consisted of 10 sessions, and after the volunteers were reevaluated. Anova Repeated Measures were used. Results: There was a 40.1% reduction in pain level, a 13.6% increase in trunk extensor strength, and a decrease in contraction between rectus abdominis and iliocostalis for GDL after treatment. Conclusion: 10 sessions of cupping therapy assist in reducing pain and improving trunk strength in young people with lower back pain.